Length-based stock assessment in small-scale multi-gear fisheries: insights from a European hotspot (NW Spain) - Daniel García-García; Marta Cousido-Rocha; Rafael Bañón; José Manuel Campelos; Fernando Quintero; Asunción Gancedo; Fabio Lamas; Alberto Otero; Angel Rodríguez; Alexandre Alonso-Fernández (Reviews in Fish Biology and Fisheries, 2026)

Development of fluorescence and colorimetric LAMP-based assays for rapid and sensitive detection of toxigenic Bacillus cereus group strains in plant-based products - Marta Bisaschi; Alessandra Fontana; Maria Luisa Callegari; Antonio Del Casale; Lorenzo Morelli; Alexandre Lamas; Marta Prado; Vania Patrone (Food Control, 2026)

Protocol development for an efficient digitization of palaeontological heritage: The case of Camp dels Ninots fossil site (Spain) - Adriana Linares-Martín; Bruno Gómez de Soler; Roy M. Farman; Elena Moreno-Ribas; Pablo Mateos Prieto; Marta Fontanals; Andrea Alías; Javier Sopesens; Hugues-Alexandre Blain; Gerard Campeny Vall-llosera (Geoheritage, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Living Near the Surface: Dive Behavior of Sei Whales ( Balaenoptera borealis ) in the Southwestern Atlantic Ocean - Clarêncio Gomes Baracho‐Neto; Leonardo Liberali Wedekin; David Haas; Lucas Lima de Oliveira; Marta Jussara Cremer; Alexandre Novaes Zerbini (Marine Mammal Science, 2026)
Understanding the diving behavior of baleen whales in tropical breeding areas is essential for evaluating both ecological functions and anthropogenic threats. In this study, we combined satellite transmitters and generalized additive mixed models (GAMMs) to investigate the dive behavior of sei whales ( Balaenoptera borealis ) in Santos Basin (SB), off southeastern Brazil. A total of 9963 dives were analyzed, revealing a dominance of shallow dives, with 93% of dives occurring at depths ≤ 20 m. Environmental variables such as sea surface temperature, local bathymetry, and chlorophyll concentration significantly influenced dive depth and duration. Cooler waters and deeper offshore areas were associated with longer and deeper dives, while higher surface productivity (indicated by increased chlorophyll a levels) shortened dive times. Behavioral and temporal covariates, including diel period, lunar phase, and dive shape, further modulated diving patterns. The prevalence of shallow diving behavior within the depth range of vessel drafts (≤ 20 m) raises significant conservation concerns, particularly regarding the risk of ship strikes in high‐traffic areas like the Santos Basin. Our findings highlight the behavioral plasticity of sei whales in tropical low‐latitude habitats and emphasize the importance of integrating dive behavior data into marine spatial planning and mitigation strategies. Reducing vessel speed and rerouting traffic in high‐density whale habitats should be considered in the future with further studies to reduce the risk of anthropogenic impacts on this threatened species.

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Natural deep eutectic systems-based Ginkgo biloba extracts: A natural and sustainable solution for skin care - Marta Marques; Ana Rita Jesus; Ana Rita C. Duarte; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2025)

Novel unsupervised Bayesian method for Near Real-Time forest loss detection using Sentinel-1 SAR time series: Assessment over sampled deforestation events in Amazonia and the Cerrado - Marta Bottani; Laurent Ferro-Famil; Juan Doblas Prieto; Stéphane Mermoz; Alexandre Bouvet; Thierry Koleck; Thuy Le Toan (Remote Sensing of Environment, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

In vitro gastrointestinal digestion of broccolis sprout extract: Impact on the bioaccesibility of sulforaphane and total phenolic - Vívian de Vasconcelos Lopes; Flávia Oliveira Brito; Jean de Oliveira Lopes; Giovanna Alexandre Fabiano; Carolina Lazarone Soares; Marta Citelli; Lilia Zago; Adriane Elisabete Costa Antunes; Marie Evans; Peter Stenvinkel; Carla Maria Avesani; Roberta Fontanive Miyahira (Food Research International, 2025)

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Soil characteristics drive contrasting patterns of association between symbiotic rhizobia of endemic and widespread Mimosa species in Brazil - Luc Rouws; Alexandre Barauna; Chrizelle Beukes; Janaina R.C. Rouws; Sergio Miana de Faria; Eduardo Gross; Fabio Bueno dos Reis; Marcelo F. Simon; Marta Maluk; David W. Odee; Stephanie Fordeyn; Gregory Kenicer; et al. (Applied Soil Ecology, 2024)

Variability of faecal microbiota and antibiotic resistance genes in flocks of migratory gulls and comparison with the surrounding environment - Dayana Jarma; Oriol Sacristán-Soriano; Carles M. Borrego; Francisco Hortas; Juan M. Peralta-Sánchez; José L. Balcázar; Andy J. Green; Esteban Alonso; Alexandre Sánchez-Melsió; Marta I. Sánchez (Environmental Pollution, 2024)

Selective inhibition of HDAC6 by N-acylhydrazone derivative reduces the proliferation and induces senescence in carcinoma hepatocellular cells - Guilherme Álvaro Ferreira-Silva; Daniel Alencar Rodrigues; Carolina Girotto Pressete; Ester Siqueira Caixeta; Angel Mauricio Castro Gamero; Marta Miyazawa; João Adolfo Costa Hanemann; Carlos Alberto Manssour Fraga; Alexandre Ferro Aissa; Marisa Ionta (Toxicology in Vitro, 2024)

Advancing air quality monitoring: A low-cost sensor network in motion – Part I - Carolina Correia; Pedro Santana; Vânia Martins; Pedro Mariano; Alexandre Almeida; Susana Marta Almeida (Journal of Environmental Management, 2024)

Edible hydrosoluble sachets produced with food by-products and natural additives - Alexandre M.S. Jorge; Cristiana S.A. Bento; Marta H.F. Henriques; Marisa C. Gaspar; Mara E.M. Braga (Food Hydrocolloids, 2024)

Assessment of the presence of Acinetobacter spp. resistant to β-lactams in commercial ready-to-eat salad samples - Ana Costa-Ribeiro; Sarah Azinheiro; Sandra Mota; Marta Prado; Alexandre Lamas; Alejandro Garrido-Maestu (Food Microbiology, 2024)

Winged resistance: Storks and gulls increase carriage of antibiotic resistance by shifting from paddy fields to landfills - Oriol Sacristán-Soriano; Dayana Jarma; Marta I. Sánchez; Noelia Romero; Esteban Alonso; Andy J. Green; Alexandre Sànchez-Melsió; Francisco Hortas; José Luis Balcázar; Juan Manuel Peralta-Sánchez; Carles M. Borrego (Science of The Total Environment, 2024)

Exploring the neuroprotective potential of antimicrobial peptides from Dinoponera quadriceps venom against pentylenetetrazole-induced seizures in vivo - Livia Correia Fernandes Paes; Dânya Bandeira Lima; Daniel Moreira Alves da Silva; José Tiago Valentin; Pedro Everson Alexandre de Aquino; Alicia Belén García-Jareño; Mar Orzaéz; Marta Maria de França Fonteles; Alice Maria Costa Martins (Toxicon, 2024)

Paleosol marked by contrasting formation processes: A pilot study using digital morphometrics in Southeastern Brazil - Fernanda Almeida Bócoli; Sérgio Henrique Godinho Silva; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Alexandre Uezu; Marco Aurélio Carbone Carneiro; Marta Vasconcelos Ottoni; et al. (CATENA, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

N-acylhydrazone derivative modulates cell cycle regulators promoting mitosis arrest and apoptosis in estrogen positive MCF-7 breast cancer cells - Melissa Lúcia Melo; Rafael Fonseca; Fernanda Pauli; Bruno Zavan; João Adolfo Costa Hanemann; Marta Miyazawa; Ester Siqueira Caixeta; Júlia Louise Moreira Nacif; Alexandre Ferro Aissa; Eliezer J. Barreiro; Marisa Ionta (Toxicology in Vitro, 2023)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Phage amplification coupled with loop-mediated isothermal amplification (PA-LAMP) for same-day detection of viable Salmonella Enteritidis in raw poultry meat - Alexandre Lamas; Sílvio B. Santos; Marta Prado; Alejandro Garrido-Maestu (Food Microbiology, 2023)

Edible films produced from agrifood by-products and wastes - Alexandre M.S. Jorge; Marisa C. Gaspar; Marta H.F. Henriques; Mara E.M. Braga (Innovative Food Science & Emerging Technologies, 2023)

Evaluation of Covalent Organic Frameworks for the low-cost, rapid detection of Shiga Toxin-producing Escherichia coli in ready-to-eat salads - Ana Costa-Ribeiro; Sarah Azinheiro; Soraia P.S. Fernandes; Alexandre Lamas; Marta Prado; Laura M. Salonen; Alejandro Garrido-Maestu (Analytica Chimica Acta, 2023)

Aerial photogrammetry techniques using drones to estimate morphometric measurements and body condition in South American small cetaceans - Lucas L. de Oliveira; Artur Andriolo; Marta J. Cremer; Alexandre N. Zerbini (Marine Mammal Science, 2023)
Aerial photogrammetry protocols using drones have proved efficient in monitoring free‐living cetaceans. In this work an aerial photogrammetry protocol using a drone was applied to estimate morphometric measurements and body condition variation in two endangered cetacean species, franciscanas ( Pontoporia blainvillei , n = 122) and Guiana dolphin ( Sotalia guianensis , n = 41). Sampling occurred in winter and summer in Babitonga Bay, southern Brazil. A 115 cm length object was used to calibrate the scale of measurements at different altitudes. A scale calibration model based on eGSD regression by flight altitude was developed ( RMSE = 0.039, r 2 = 0.9902, ΔAICc = 0.00) and used to convert measurements from pixels to centimeters. Five morphometric measurements (body length ‐ BL, widths at anterior pectoral fin ‐ AP, axilla ‐ AX, anterior dorsal fin ‐ AD, and posterior dorsal fin ‐ PD) were taken from each animal to infer body condition, in which, the widths in the anterior portions of the body as % BL, can be an auxiliary tool in the evaluation of variation in the body condition of the small cetaceans studied. The aerial photogrammetry protocol allowed for estimating morphometric measurements and monitoring seasonal changes in the body condition of the small cetaceans.

Musa spp. cultivars as a neutralising source against some toxic activities of Bothrops and Crotalus genus snake venoms - Márcia Matos da Silva; Gerso Pereira Alexandre; Marta Regina Magalhães; Ana Maria Torres; Lucilia Kato; Victória Costa da Silva; Simone Maria Teixeira de Saboia Morais; Armando Garcia Rodriguez; Taícia Pacheco Fill; Alana Kelyene Pereira; Jussara Roque; Jorge Luiz Souza Simão; et al. (Toxicon, 2023)

Mixing methods for solid state electrodes: Techniques, fundamentals, recent advances, and perspectives - Leire Fernandez-Diaz; Julen Castillo; Elene Sasieta-Barrutia; Maria Arnaiz; Marta Cabello; Xabier Judez; Alexandre Terry; Laida Otaegui; Maria C. Morant-Miñana; Aitor Villaverde (Chemical Engineering Journal, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Long‐term unsustainable patterns of development rather than recent deforestation caused the emergence of Orthocoronavirinae species - Sérvio P. Ribeiro; Debmalya Barh; Bruno Silva Andrade; Raner José Santana Silva; Diogo Henrique Costa‐Rezende; Paula Luize Camargos Fonseca; Sandeep Tiwari; Marta Giovanetti; Luiz Carlos Junior Alcantara; Vasco Ariston Azevedo; Preetam Ghosh; José Alexandre F. Diniz‐Filho; et al. (Environmental Microbiology, 2022)
We investigated whether a set of phylogeographical tracked emergent events of Orthocoronavirinae were related to developed, urban and polluted environments worldwide. We explored coronavirus records in response to climate (rainfall parameters), population density, CO 2 emission, Human Developmental Index (HDI) and deforestation. We contrasted environmental characteristics from regions with spillovers or encounters of wild Orthocoronavirinae against adjacent areas having best‐preserved conditions. We used all complete sequenced CoVs genomes deposited in NCBI and GISAID databases until January 2021. Except for Deltacoronavirus, concentrated in Hong Kong and in birds, the other three genera were scattered all over the planet, beyond the original distribution of the subfamily, and found in humans, mammals, fishes and birds, wild or domestic. Spillovers and presence in wild animals were only reported in developed/densely populated places. We found significantly more occurrences reported in places with higher HDI, CO 2 emission, or population density, along with more rainfall and more accentuated seasonality. Orthocoronavirinae occurred in areas with significantly higher human populations, CO 2 emissions and deforestation rates than in adjacent locations. Intermediately disturbed ecosystems seemed more vulnerable for Orthocoronavirinae emergence than forested regions in frontiers of deforestation. Sadly, people experiencing poverty in an intensely consumerist society are the most vulnerable.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Occurrence but not intensity of mortality rises towards the climatic trailing edge of tree species ranges in European forests - Alexandre Changenet; Paloma Ruiz‐Benito; Sophia Ratcliffe; Thibaut Fréjaville; Juliette Archambeau; Annabel J. Porte; Miguel A. Zavala; Jonas Dahlgren; Aleksi Lehtonen; Marta Benito Garzón (Global Ecology and Biogeography, 2021)
Aim Tree mortality is increasing world‐wide, leading to changes in forest composition and altering global biodiversity. Nonetheless, owing to the multifaceted stochastic nature of tree mortality, large‐scale spatial patterns of mortality across species ranges and their underlying drivers remain difficult to understand. Our main goal was to describe the geographical patterns and drivers of the occurrence of mortality (presence of a mortality event) and the intensity of tree mortality (amount of mortality related to that mortality event) in Europe. We hypothesized that the occurrence of mortality represents background mortality and is higher in the margin than in core populations, whereas the intensity of mortality could have a more even distribution according to the spatial and temporal stochasticity of die‐off events. Location Europe (Spain, France, Germany, Belgium, Sweden and Finland). Major taxa studied More than 1.5 million trees belonging to 20 major forest tree species. Methods We developed binomial and truncated negative binomial models to tease apart the occurrence and intensity of tree mortality in National Forest Inventory plots at the range‐wide scale. The occurrence of mortality indicated that at least one tree had died in the plot, whereas the intensity of mortality referred to the number of dead trees per plot. Results The highest occurrence of mortality was found in peripheral regions and the climatic trailing edge linked with drought, whereas the intensity of mortality was driven by competition, drought and high temperatures and was scattered uniformly across species ranges. Main conclusions We show that tree background mortality, but not die‐off, is generally higher in the trailing‐edge populations. It remains to be explored whether other demographic traits, such as growth, reproduction and regeneration, also decrease at the trailing edge of European tree populations.

Adsorption of bisphenol A by activated carbon developed from PET waste by KOH activation - Vicente Gómez-Serrano; Marta Adame-Pereira; María Alexandre-Franco; Carmen Fernández-González (Environmental Science and Pollution Research, 2021)

Characterization of wood from Schizolobium parahyba var. amazonicum Huber × Ducke trees from a multi-stratified agroforestry system established in the Amazon rainforest - Adriano Reis Prazeres Mascarenhas; Marta Silvana Volpato Sccoti; Rafael Rodolfo de Melo; Fernando Luiz de Oliveira Corrêa; Emanuel Fernando Maia de Souza; Alexandre Santos Pimenta (Agroforestry Systems, 2021)

CPAMD8 loss-of-function underlies non-dominant congenital glaucoma with variable anterior segment dysgenesis and abnormal extracellular matrix - Juan-Manuel Bonet-Fernández; José-Daniel Aroca-Aguilar; Marta Corton; Ana-Isabel Ramírez; Susana Alexandre-Moreno; María-Teresa García-Antón; Juan-José Salazar; Jesús-José Ferre-Fernández; Raquel Atienzar-Aroca; Cristina Villaverde; Ionut Iancu; Alejandra Tamayo; et al. (Human Genetics, 2020)

Humans do matter: determinants of red fox (Vulpes vulpes) presence in a western Mediterranean landscape - Marta Alexandre; Dário Hipólito; Eduardo Ferreira; Carlos Fonseca; Luís Miguel Rosalino (Mammal Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Human activity is altering the world’s zoogeographical regions - Rubén Bernardo‐Madrid; Joaquín Calatayud; Manuela González‐Suárez; Martin Rosvall; Pablo M. Lucas; Marta Rueda; Alexandre Antonelli; Eloy Revilla (Ecology Letters, 2019)
Zoogeographical regions, or zooregions, are areas of the Earth defined by species pools that reflect ecological, historical and evolutionary processes acting over millions of years. Consequently, researchers have assumed that zooregions are robust and unlikely to change on a human timescale. However, the increasing number of human‐mediated introductions and extinctions can challenge this assumption. By delineating zooregions with a network‐based algorithm, here we show that introductions and extinctions are altering the zooregions we know today. Introductions are homogenising the Eurasian and African mammal zooregions and also triggering less intuitive effects in birds and amphibians, such as dividing and redefining zooregions representing the Old and New World. Furthermore, these Old and New World amphibian zooregions are no longer detected when considering introductions plus extinctions of the most threatened species. Our findings highlight the profound and far‐reaching impact of human activity and call for identifying and protecting the uniqueness of biotic assemblages.

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Habitat structure shaping megabenthic communities inhabiting subtidal soft bottoms along the Algarve coast (Portugal) - Marta M. Rufino; Alexandre M. Pereira; Fábio Pereira; Paula Moura; Paulo Vasconcelos; Miguel B. Gaspar (Hydrobiologia, 2017)

A multi-environment trials diallel analysis provides insights on the inheritance of fumonisin contamination resistance in tropical maize - José Maria Villela Pádua; Kaio Olímpio Das Graças Dias; Maria Marta Pastina; João Cândido de Souza; Valéria Aparecida Vieira Queiroz; Rodrigo Veras da Costa; Maria Beatriz Pereira da Silva; Carlos Alexandre Gomes Ribeiro; Claudia Teixeira Guimarães; Salvador Alejandro Gezan; Lauro José Moreira Guimarães (Euphytica, 2016)

First record of Pelobates syriacus (Anura, Amphibia) in the early Pleistocene of Italy - Hugues-Alexandre Blain; Massimo Delfino; Claudio Berto; Marta Arzarello (Palaeobiodiversity and Palaeoenvironments, 2016)

Quality assessment of sulfurous thermal waters in the city of Poços de caldas, Minas gerais, Brazil - Adriana Moneira de Carvalho; Marta Cristina Teixeira Duarte; Alexandre Nunes Ponezi (Environmental Monitoring and Assessment, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

NrsZ : a novel, processed, nitrogen‐dependent, small non‐coding RNA that regulates P seudomonas aeruginosa PAO 1 virulence - Nicolas Wenner; Alexandre Maes; Marta Cotado‐Sampayo; Karine Lapouge (Environmental Microbiology, 2014)
Summary The opportunistic pathogen P seudomonas aeruginosa PAO1 has a remarkable capacity to adapt to various environments and to survive with limited nutrients. Here, we report the discovery and characterization of a novel small non‐coding RNA : NrsZ (nitrogen‐regulated sRNA ). We show that under nitrogen limitation, NrsZ is induced by the NtrB / C two‐component system, an important regulator of nitrogen assimilation and P . aeruginosa's swarming motility, in concert with the alternative sigma factor RpoN . Furthermore, we demonstrate that NrsZ modulates P . aeruginosa motility by controlling the production of rhamnolipid surfactants, virulence factors notably needed for swarming motility. This regulation takes place through the post‐transcriptional control of rhlA , a gene essential for rhamnolipids synthesis. Interestingly, we also observed that NrsZ is processed in three similar short modules, and that the first short module encompassing the first 60 nucleotides is sufficient for NrsZ regulatory functions.

Community phylogenetics at the biogeographical scale: cold tolerance, niche conservatism and the structure of N orth A merican forests - Bradford A. Hawkins; Marta Rueda; Thiago F. Rangel; Richard Field; José Alexandre F. Diniz‐Filho (Journal of Biogeography, 2014)
Aim The fossil record has led to a historical explanation for forest diversity gradients within the cool parts of the Northern Hemisphere, founded on a limited ability of woody angiosperm clades to adapt to mid‐Tertiary cooling. We tested four predictions of how this should be manifested in the phylogenetic structure of 91,340 communities: (1) forests to the north should comprise species from younger clades (families) than forests to the south; (2) average cold tolerance at a local site should be associated with the mean family age (MFA) of species; (3) minimum temperature should account for MFA better than alternative environmental variables; and (4) traits associated with survival in cold climates should evolve under a niche conservatism constraint. Location The contiguous U nited S tates. Methods We extracted angiosperms from the US Forest Service's Forest Inventory and Analysis database. MFA was calculated by assigning age of the family to which each species belongs and averaging across the species in each community. We developed a phylogeny to identify phylogenetic signal in five traits: realized cold tolerance, seed size, seed dispersal mode, leaf phenology and height. Phylogenetic signal representation curves and phylogenetic generalized least squares were used to compare patterns of trait evolution against Brownian motion. Eleven predictors structured at broad or local scales were generated to explore relationships between environment and MFA using random forest and general linear models. Results Consistent with predictions, (1) southern communities comprise angiosperm species from older families than northern communities, (2) cold tolerance is the trait most strongly associated with local MFA, (3) minimum temperature in the coldest month is the environmental variable that best describes MFA, broad‐scale variables being much stronger correlates than local‐scale variables, and (4) the phylogenetic structures of cold tolerance and at least one other trait associated with survivorship in cold climates indicate niche conservatism. Main conclusions Tropical niche conservatism in the face of long‐term climate change, probably initiated in the Late Cretaceous associated with the rise of the Rocky Mountains, is a strong driver of the phylogenetic structure of the angiosperm component of forest communities across the USA . However, local deterministic and/or stochastic processes account for perhaps a quarter of the variation in the MFA of local communities.

Global richness patterns of venomous snakes reveal contrasting influences of ecology and history in two different clades - Levi Carina Terribile; Miguel Ángel Olalla-Tárraga; Ignacio Morales-Castilla; Marta Rueda; Rosa M. Vidanes; Miguel Ángel Rodríguez; José Alexandre Felizola Diniz-Filho (Oecologia, 2009)

First record of Albunea carabus (Decapoda, Anomura, Hippidea) from the Algarve coast, South Portugal - Alexandre M. Pereira; Marta M. Rufino; Miguel B. Gaspar (Marine Biology Research, 2008)

Western Style Diet Impairs Entrance of Blood-Borne Insulin-like Growth Factor-1 into the Brain - Marcelo O. Dietrich; Alexandre Muller; Marta Bolos; Eva Carro; Marcos L. Perry; Luis V. Portela; Diogo O. Souza; Ignacio Torres-Aleman (NeuroMolecular Medicine, 2007)